Analisis Kompetensi Tenaga Kerja pada Konstruksi Gedung - Sriwinda Imran; Sartika Dewi Usman; Mohammad Yusuf Tuloli (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
The quality of building construction is significantly influenced by the competence of the workforce involved. Competent labor plays a pivotal role in determining the success or failure of a construction project, as workers are directly responsible for implementing the planned design. This study aims to assess the competence of construction workers engaged in building construction, with a focus on blacksmith construction workers, carpenters, and concrete workers involved in the Hulondalo and Exhibition Center (HBEC) project in Gorontalo City. Employing a descriptive qualitative approach, the research examines workers performing column and beam structure work, which are critical components of the building’s structural integrity. Competence is analyzed based on three key aspects: knowledge, work abilities, and work attitudes. The findings reveal that the majority of construction workers in the HBEC project possess basic-level competencies, with 90% classified at Level 1 and only 10% at Level 2. Level 1 indicates workers with fundamental skills who require supervision and guidance, while Level 2 represents those capable of working with moderate independence and a higher degree of technical understanding. The results highlight the importance of targeted training and capacity-building initiatives to improve worker competence, thereby ensuring higher quality and efficiency in building construction. This study underscores the need for continuous skills development in the construction sector to meet the demands of increasingly complex building projects.